2011
DOI: 10.17969/agripet.v11i2.368
|View full text |Cite
|
Sign up to set email alerts
|

Efek Pemberian Ekstrak Jaloh Dikombinasi dengan Probiotik dan Kromium Terhadap Profil Hematologi dan Titer Antibodi Vaksin ND pada Ayam Broiler yang Mengalami Stres Panas

Abstract: The purpose of this study is to determine the respons of chicken broiler under heat stress that given drinking water contained extract jaloh combined with probiotic and Cr mineral in the profile of haematology and antibody respons of Newcastle Disease vaccine. Twenty four of 20-day old Cobb broiler chickens were randomly assigned and devided to 6 treatment groups. Completely randomized design was used in this study. The treatments were as follows: 1) chickens under heat stress, given jaloh extract, probiotic, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0
3

Year Published

2012
2012
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 11 publications
0
1
0
3
Order By: Relevance
“…Sugito et al (2010) reported that giving jaloh stem bark extract per se at the dose of 1.000 mg/l in drinking water or combined it with chromium given two hours before cage temperature reaching 33 ± 1 o C could prevent chickens from losing their body weight. Added by Sugito et al (2011), giving jaloh stem bark extract combined with probiotic and chromium (Cr) had no significant effect in hematology profile but when combined with only Cr, broiler had potential capability to stimulate improvement built of antibody as immunomodulation under heat stress.…”
Section: Mortalitymentioning
confidence: 99%
“…Sugito et al (2010) reported that giving jaloh stem bark extract per se at the dose of 1.000 mg/l in drinking water or combined it with chromium given two hours before cage temperature reaching 33 ± 1 o C could prevent chickens from losing their body weight. Added by Sugito et al (2011), giving jaloh stem bark extract combined with probiotic and chromium (Cr) had no significant effect in hematology profile but when combined with only Cr, broiler had potential capability to stimulate improvement built of antibody as immunomodulation under heat stress.…”
Section: Mortalitymentioning
confidence: 99%
“…Ayam broiler merupakan ayam yang sangat rentan terhadap perubahan suhu lingkungan yang ekstrim. Ayam broiler memiliki suhu dan kelembaban optimal untuk menunjang pertumbuhan yaitu berkisar, 20-25℃ dan 50 -70% (Sugito et al, 2011). Ayam broiler memiliki efisiensi dalam mengubah pakan menjadi daging yang baik serta pertumbuhannya cepat, ayam broiler juga mudah mengalami stres apabila suhu lingkungan tinggi (Setiaji dan Sudarman, 2006).…”
Section: Pendahuluanunclassified
“…Sugito et al (2010) melaporkan pemberian ekstrak kulit batang jaloh secara tunggal atau kombinasi dengan mineral kromium (Cr) dalam air minum dapat mengurangi dampak cekaman panas pada ayam sehingga akan memperbaiki performa ayam broiler. Ditambahkan Sugito et al (2011) bahwa pemberian ekstrak jaloh baik secara tunggal atau kombinasi dengan probiotik dan Cr tidak mempengaruhi profil sel darah. Penelitian ini bertujuan mengetahui pemberian kombinasi ekstrak jaloh mineral Cr terhadap pembentukan HSP-70 dan hormon kortisol dalam serum ayam broiler yang mengalami cekaman panas.…”
Section: Cekamanunclassified